Mechanism of heavy metal uptake by electron paramagnetic resonance and FTIR: Enhanced manganese(II) removal onto waste acorn of Quercus ithaburensis - Kul, Zeynep Ekmekyapar; Nuhoglu, Yasar; Kul, Sinan; Nuhoglu, Cigdem; Torun, Fatma Ekmekyapar (TAYLOR & FRANCIS INC, 2016)
This study aimed to use waste acorn of Quercus ithaburensis (WAQI) for biosorption Mn(II) from synthetic wastewater. Parameters such as metal concentration, pH, biosorbent concentration, stirring speed, particle size, and temperature were investigated by using batch kinetic studies. The percent removal of Mn(II) with native WAQI was 66.67%, this rose to 99.97% with activation processing. The mathematical description of the biosorption equilibrium and the adsorption mechanism were examined.Thermodynamic investigations indicate that adsorption reactions are spontaneous and slightly endothermic. H degrees and S degrees were found as 2.33 kJ mol(-1) and 0.013 kJ mol(-1) K-1, respectively. The activation energy of biosorption was calculated as 6.29 kJ mol(-1).
Keywords: Mn(II) removal; treated and untreated biomass; thermodynamics; kinetics; AQUEOUS-SOLUTION; BIOSORPTION; ADSORPTION; IONS; EQUILIBRIUM; NICKEL(II); SORPTION; CR(VI); BATCH; Chemistry; Engineering